Evaluasi Kondisi Fisik Dominan dan Kemampuan Tendangan Lurus ada Atlet Pencak Silat Ilmukti Aceh Besar Tahun 2023 - Ikhwani, Yudi; Akbar, Aldiansyah; Rahman, Aulia (Journal of Technology and Literacy in Education, 2024)
Based on the background of the problem that has been described above, the problem formulation is "Evaluation of Dominant Physical Condition and Straight Kick Ability in the 2023 Aceh Besar Ilmukti Pencak Silat Athletes. Based on the problem above, the author can formulate the problem formulation as follows: (1 ) What is the level of Dominant Physical Conditions in Aceh Besar Ilmukti Pencak Silat Athletes. (2) What is the level of straight kick ability among the Aceh Besar Ilmukti Pencak Silat Athletes. The aims of this research are: (1) To determine the dominant physical condition of the 2023 Aceh Besar Pencak Silat Ilmukti Athletes. (2) To determine the straight kick ability of the 2023 Aceh Besar Ilmukti Pencak Silat Athletes. This research is included in descriptive research. type of evaluation. The population is all the subjects to be studied, the population in this study is all the Ilmukti Aceh Besar pencak silat athletes, totaling 11 people. The samples in this study were all the Ilmukti Aceh Besar pencak silat athletes who had been selected and designated as athletes. The population is only 11 people, so remembering that the sample is the entire population, it is used as a sample or total sampling. To obtain data in this study, measurement test techniques and dominant physical conditions and straight kick tests were used. The data processing technique used is calculating the average and percentage for each physical component using a formula. Based on the results of the research and discussion in the previous chapter, it can be concluded that: (1) The level of physical condition of the 2023 Aceh Besar Ilmukti Pencak Silat Athletes is in good condition. (2) The ability of the 2023 Aceh Besar Ilmukti Pencak Silat Athletes to perform straight kicks in good condition.